2022
DOI: 10.18502/sjms.v17i1.10690
|View full text |Cite
|
Sign up to set email alerts
|

Familial Facial Palsy: A Case Series of Six Families from the Northern State, Sudan

Abstract: Familial facial palsy is uncommon, accounting only for 4–14% of Bell's palsy cases. We report six families with single or recurrent episodes of familial facial palsy from Northern State, Sudan. The first family had two brothers with single episodes of Bell's palsy. The index case of the second family was a 19-year-old female who and nine other members of her family had a single or recurrent episodes of Bell's palsy. The third, fourth, fifth, and sixth families had eight, five, four, and five members, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…The total number of cases with facial palsy in this second case series was 23 with 14(60.9%) females and a female to male ratio of 1.55:1. The total number of affected cases was less and more females were affected, compared to that reported in the previous study from Northern State which showed that 34 cases from 6 families were affected with 38.2% females [10].…”
Section: Discussioncontrasting
confidence: 62%
See 3 more Smart Citations
“…The total number of cases with facial palsy in this second case series was 23 with 14(60.9%) females and a female to male ratio of 1.55:1. The total number of affected cases was less and more females were affected, compared to that reported in the previous study from Northern State which showed that 34 cases from 6 families were affected with 38.2% females [10].…”
Section: Discussioncontrasting
confidence: 62%
“…Only two female patients from two different families developed recurrent facial palsy, compared to 7 cases of recurrent facial palsy from 4 families in the previous study [10].…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations